Scale-up considerations for surface collecting agent assisted in-situ burn crude oil spill response experiments in the Arctic: Laboratory to field-scale investigations. (1st April 2017) - Bullock, Robin J.; Aggarwal, Srijan; Perkins, Robert A.; Schnabel, William
Abstract: In the event of a marine oil spill in the Arctic, government agencies, industry, and the public have a stake in the successful implementation of oil spill response. Because large spills are rare events, oil spill response techniques are often evaluated with laboratory and meso-scale experiments. The experiments must yield scalable information sufficient to understand the operability and effectiveness of a response technique under actual field conditions. Since in-situ burning augmented with surface collecting agents ("herders") is one of the few viable response options in ice infested waters, a series of oil spill response experiments were conducted in Fairbanks, Alaska, in 2014 and 2015 to evaluate the use of herders to assist in-situ burning and the role of experimental scale. This study compares burn efficiency and herder application for three experimental designs for in-situ burning of Alaska North Slope crude oil in cold, fresh waters with ∼10% ice cover. The experiments were conducted in three project-specific constructed venues with varying scales (surface areas of approximately 0.09 square meters, 9 square meters and 8100 square meters). The results from the herder assisted in-situ burn experiments performed at these three different scales showed good experimental scale correlation and no negative impact due to the presence of ice cover on burn efficiency. Experimental conclusions are predominantly associated with application of the herder material and usability for a given experiment scale to make response decisions. Graphical abstract: Highlights: In-situ burn efficiency and herder application are compared at different scales in arctic conditions. Burn efficiency results showed good experiment scale correlation. Over-application of herder indicated lowering of burn efficiency. Operational improvements for herder application in field scale trials are noted.